The historiography of the national policy and nation- and state-building of the 1920-1940s: regional aspect (the experience of Perm region) - Kamenskikh, M. S. (Perm Federal Research Centre Journal, 2019)
The article analyses the main historical works related to the history of the national state policy in the Prikamye region in the 1920s and 1930s. The author considers both general theoretical studies and those devoted to the history of certain nations and their participation in the national policies implementation. The article presents the most relevant problems of historiography, the positions of various authors on the most pressing issues. Finally, the author concludes that the existing experience of studying the history of certain nations and the introduction of new documents into scientific circulation create favorable conditions for carrying out generalizing studies on national policies in the Perm region in the first two decades of the Soviet Power.